Investigation of cytotoxic, genotoxic, and apoptotic effects of curcumin on glioma cells - Seyithanoğlu, Mehmet Hakan; Abdallah, Anas; Kitiş, Serkan; Güler, Eray Metin; Koçyiğit, Abdurrahim; Dündar, Tolga Turan; Gündağ Papaker, Meliha (Cellular and Molecular Biology, 2019)
Glioblastoma is a malignant tumor of the brain. The treatment of this tumor is still a challenge. Curcumin has been shown to have therapeutic effects when used to treat malignant diseases. However, the molecular mechanisms of its action are not fully elucidated. We hypothesized that reactive oxygen species (ROS) have a key role in curcumin-induced DNA damage, apoptosis, and cell death. To test our hypothesis, cytotoxic, genotoxic, apoptotic, and ROS-generating effects, as well as mitochondrial membrane potentials of curcumin on rat glioma cells (C-6) and normal fibroblastic cells (L-929) were investigated. We examined concentration-dependent cytotoxic, genotoxic, apoptotic, and ROS generating effects of curcumin at C-6 cells and L-929 cells. The cells were incubated with different doses of curcumin (10-100 µM) for 24 hours. Higher doses of curcumin resulted in greater cellular death of cancer than of normal cells at higher concentrations. Curcumin also induced ROS generation in cancer than normal cells in a concentration-dependent manner. Our results showed that curcumin-induced DNA damage in a dose-dependent manner (p < 0.001). At high curcumin concentration such as 80 µM, the proportions of live cells in cancer and normal cell lines were 11.5 and 44.3, respectively. The higher doses of curcumin resulted in greater apoptosis in cancer than normal cells.This in vitro study provided clear evidence that curcumin induced DNA damage and apoptosis. Cytotoxicity may be due to its pro-oxidant activity in a dose-dependent manner in cancer and normal cells. These activities were higher in cancer cells.